Selection of Independent Curriculum Implementation with the TOPSIS Method - Enok Tuti Alawiah; Dwi Andini Putri (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
The government implements learning with a new paradigm called the independent curriculum. The government gives flexibility to schools to choose three implementation paths, namely Independent Learning, Independent Change and Independent Sharing. However, schools have difficulties in determining the appropriate model. This study aims to help schools decide on the most ideal independent curriculum implementation model to be implemented in schools. The research method uses TOPSIS, which is a decision support method that can help solve multi-criteria problems by providing results that are closest to the ideal. The results of the study show that respondents chose the Independent Changing path for the implementation of an independent curriculum in educational units by considering the readiness of educational units, the availability of information technology and the teacher's desire to change